Assessing nutrient composition and digestibility of tallgrass-prairie hay - Cochran, R.C.; Olson, K. C.; Titgemeyer, Evan C.; Jones, Timothy J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirteen steers were used in a 4 13 incomplete Latin square to determine chemical composition and digestibility for 13 samples of tallgrass prairie hay. Hays were collected from a variety of locations in east-central Kansas and represented a wide array of harvest dates and storage conditions. Steers were fed prairie hay and soybean meal at 1.5% and .2% of body weight, respectively, to equalize intakes relative to body weight and prevent degradable intake protein (DIP) from limiting extent of digestion. Prairie hay samples were analyze d for N, ADIN, ADF, NDF, ADIA, monosaccharides (sugars), and alkali-labile phenolic acids (lignin components). The relationships of various forage chemical components to diet organic matter digestibility (OMD) were examined using simple, linear regression. There was a close relationship between OMD and ADF (r 2 = .62; OMD = .822 [ADF] + 96.47). In addition, the ratio of xylose:glucose (r2 = .62; OMD = 41.93[X:G] + 94.14) explained significant amounts of the variation in OMD. Defining the chemical composition of bluestem hay may be of value in predicting organic matter digestibility and, ultimately, energetic value.
Keywords: Beef; Hay digestibility; Hay chemical composition; Forage